Culture and communication : bows as special class ofunverbal means of intercourse - Бердалиева, Р. Ш. (Eurasian Journal of Philology Science and Education, 2016)
In the article the problem of unverbal cooperation of peopleis examined as one of meaningful components of cross cultural communication. The Unverbal side of commonunication, in spite of the importance in aninformation transfer, often remains out of eyeshot man, although we intuitively know about that, what ever not asingle cooperation passes without their participation. Among the enormous amount of gestures and different the special class is made by bows. Bowshave the national and cultural specific, special maintenanceand execution, possess the specific informing loading in acommonunication. The bows of different people, including Kazakh national bows, are described in the article. The Kazakh bows are based on basic principles of Kazakh etiquette system of moral options of traditional society: honouring elders on age and to social status, hospitality, tolerance.